Method for simulating aging deterioration trend of weak interlayer based on variable temperature organic material

CN122944211APending Publication Date: 2026-10-20CHONGQING UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611039415.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0029]本发明以EVO有机材料构建软弱夹层,利用有机材料力学性能对温度的响应特性,通过梯度升温实现软弱夹层抗剪强度的连续、可控劣化。相比传统试验方法中夹层强度一经成型便无法改变的弊端,本发明在试验全过程中均可通过温控系统实时调节夹层强度,更贴合实际工程中软弱夹层抗剪强度随时间的渐进衰减特征。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of physical model testing technology in geotechnical engineering, and discloses a method for simulating the time-related deterioration trend of weak interlayers based on variable-temperature organic materials. The method includes: determining the geometric similarity ratio, unit weight similarity ratio, stress similarity ratio, cohesion similarity ratio, internal friction angle similarity ratio, and time similarity ratio of the physical model according to similarity ratio theory; preparing materials to simulate various lithological strata of the slope, and determining the proportion of each lithological stratum material through mechanical tests of specimen blocks; preparing a model trench; casting each lithological stratum material in layers in the model trench, and using organic materials to form weak interlayers at predetermined layers to construct the slope physical model; and installing heating components inside the weak interlayers. This invention can accurately simulate the time-related deterioration trend of weak interlayers in slopes, with strong controllability of experimental operation and high data accuracy, providing reliable experimental basis for slope stability evaluation and disaster prevention in geotechnical engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of geotechnical engineering physical model testing technology, and in particular to a method for simulating the aging deterioration trend of weak interlayers based on variable-temperature organic materials. Background Technology

[0002] In geotechnical engineering, slope instability and failure are often closely related to the strength degradation over time of weak interlayers. Weak interlayers refer to layered structural planes in rock masses with low strength and poor mechanical properties. Their shear strength gradually decreases with changes in environmental factors (such as changes in moisture content, wet-dry cycles, and temperature fluctuations), and they are the core contributing factor to slope slippage, collapse, and other disasters. In southwestern my country, slopes containing shale and mudstone interlayers are widely distributed in water conservancy, highway, and railway engineering projects. Accurately evaluating the long-term stability of such slopes is an important issue.

[0003] Currently, numerous studies have been conducted by scholars both domestically and internationally on physical model tests for the deterioration of weak interlayers in slopes. For example, Chinese invention patent CN113108752B discloses a slope model containing weak interlayers and a method for monitoring deformation during shaping. This method uses a syringe and grouting pipe to quantitatively inject grout into the interlayer soil to simulate soil interlayers of different strengths, and deploys deformation sensors within the interlayer to monitor horizontal and vertical displacement. Chinese utility model patent CN218956580U discloses an experimental system for an ice-rock debris slope model under freeze-thaw cycles. This system uses a temperature control module to simulate temperature changes and a water supply module to simulate rainfall, achieving indoor simulation of slope failure under freeze-thaw cycles. Chinese invention patent application CN113324988A discloses a variable slope simulation device for slope interface instability caused by the mudification of soft rock interlayers under alternating wet and dry conditions. This device adjusts the slope using a rotating slope test chamber and analyzes the degree of mudification in the soft rock interlayer using pH test strips.

[0004] However, the aforementioned existing technologies still have the following shortcomings:

[0005] First, the methods for controlling the strength of weak interlayers are limited and lack controllability. In existing physical model tests, once the strength of the weak interlayer material is determined, it is difficult to adjust it gradually during the test. Although some devices can change the interlayer strength before model formation by grouting, they cannot achieve continuous and controllable degradation of the interlayer strength during the test, making it difficult to realistically simulate the gradual decay of the shear strength of weak interlayers over time during long-term service.

[0006] Secondly, there is a lack of precise simulation methods for the aging degradation process of weak interlayers. Existing experimental methods mostly focus on the impact of single environmental factors such as freeze-thaw cycles and wet-dry cycles on the overall stability of slopes, failing to quantitatively simulate the aging degradation of weak interlayers as an independent research object. The aging degradation of weak interlayers is a gradual, time-dependent, long-term process, and existing devices are unable to reproduce this long-term evolution pattern on a laboratory scale.

[0007] Third, existing experimental methods cannot accurately determine the critical conditions under which the strength of the weak interlayer deteriorates to the point of slope failure. Due to the lack of real-time, non-destructive monitoring methods for the interlayer strength, it is difficult to accurately record the strength value of the weak interlayer at the moment of slope failure during the experiment, resulting in significant uncertainty in determining the critical strength threshold.

[0008] To address the aforementioned problems, this invention proposes a method for simulating the aging degradation trend of weak interlayers based on variable-temperature organic materials. Summary of the Invention

[0009] To address the technical problems mentioned in the background section, this invention provides a method for simulating the aging degradation trend of weak interlayers based on variable-temperature organic materials.

[0010] This invention is achieved using the following technical solution: a method for simulating the aging degradation trend of weak interlayers based on variable-temperature organic materials, comprising:

[0011] Step 1: Determine the geometric similarity ratio, density similarity ratio, stress similarity ratio, cohesion similarity ratio, internal friction angle similarity ratio, and time similarity ratio of the physical model based on the similarity ratio theory;

[0012] Step 2: Prepare materials for simulating various lithological strata of the slope, and determine the proportion of materials for each lithological stratum through mechanical tests of specimen blocks;

[0013] Step 3: Prepare the model trench; pour the lithological strata materials in layers into the model trench, and use organic materials to pour the weak interlayers at the predetermined layers to construct the slope physical model.

[0014] Step 4: Install heating components inside the weak interlayer and connect the heating components to a temperature controller to form a temperature control system; install resistance strain gauges at the top of the weak interlayer and the slope physical model, respectively.

[0015] Step 5: Curing the slope physical model;

[0016] Step 6: Start the temperature control system and raise the temperature of the weak interlayer according to the preset heating rate, while simultaneously recording the displacement data of each resistance strain gauge and the temperature data of the weak interlayer.

[0017] Step 7: When the slope displacement reaches the preset failure criterion, determine the critical strength of the weak interlayer according to the temperature-strength correspondence of organic materials.

[0018] Furthermore, the geometric similarity ratio is 1:300; the specific gravity similarity ratio is 1:1; the stress similarity ratio and the cohesion similarity ratio are both 1:300; the internal friction angle similarity ratio is 1:1; and the time similarity ratio is 1:20. The time similarity ratio is calculated using the Froude similarity algorithm.

[0019] Furthermore, the proportions of materials for each lithological stratum were determined through mechanical tests on specimen blocks. Specifically, cylindrical specimen blocks with a radius of 50 mm and a height of 100 mm were prepared according to a preset proportion of barite powder, gypsum, and glycerol. Three specimen blocks were prepared for each proportion. After curing, uniaxial compression tests were conducted to determine the specific gravity, compressive strength, and modulus of elasticity. A proportion-strength curve was plotted to ensure that the specific gravity was close to that of the actual stratum and that the compressive strength, after stress similarity ratio conversion, was close to that of the actual stratum. The proportions of materials for each lithological stratum were then determined. The rock types of the lithological stratum materials included limestone, karst breccia, dolomite, soft yellow fill, and weathered soil.

[0020] Furthermore, the dimensions of the slope physical model are 1m × 1.6m × 0.4m, and the dimensions of the model trench are 1.2m × 1.7m × 0.45m;

[0021] Preparing the model tank specifically includes: coating the sidewall glass surface of the model tank with Vaseline, drawing grid lines on the sidewall glass, laying a plastic film at the bottom of the model tank, and marking each lithological stratum on the model tank.

[0022] Furthermore, the lithological strata materials are poured in layers in the model trench, specifically including: making a model plate according to the stratum boundary line, using the model plate to fit the wavy stratum boundary, pouring and compacting the mixed material in layers; after completing the pouring of one stratum, roughening the surface of the poured stratum before pouring the next stratum; after each stratum is poured, marking the stratum boundary line on the side plate of the model trench.

[0023] Furthermore, the weak interlayer is formed by casting organic materials, specifically including: casting the weak interlayer using a two-stage casting method, the first casting forming the bottom layer of the weak interlayer, the heating component being laid flat on top of the bottom layer, and then the second casting forming the top layer of the weak interlayer, so that the heating component is wrapped inside the weak interlayer.

[0024] Furthermore, the heating component is a temperature heating wire, which is spirally laid inside the weak interlayer, with a spacing of 0.1m between the inner and outer layers of the spiral laying.

[0025] Furthermore, resistance strain gauges are respectively installed at the top of the weak interlayer and the slope physical model, specifically including: embedding a resistance strain gauge at the upper end of the weak interlayer, installing a resistance strain gauge at the front edge, middle and rear of the weak interlayer, and embedding a resistance strain gauge at the top of the slope.

[0026] Furthermore, the preset failure criterion is that the displacement at the top of the slope exceeds 1% of the height of the slope physical model.

[0027] Furthermore, the temperature-strength relationship of the organic material is obtained through a pre-conducted temperature-strength calibration test: standard specimens are made using organic materials with the same proportion as those used in the weak interlayer casting, and direct shear tests are conducted under different temperature conditions to determine the shear strength at each temperature point and plot the temperature-strength curve.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0029] This invention constructs a weak interlayer using EVO organic material. Utilizing the temperature-responsive characteristics of the organic material's mechanical properties, it achieves continuous and controllable degradation of the shear strength of the weak interlayer through gradient heating. Compared to traditional testing methods where the interlayer strength cannot be changed once formed, this invention allows for real-time adjustment of the interlayer strength via a temperature control system throughout the testing process, better reflecting the gradual decay of the shear strength of weak interlayers over time in actual engineering applications.

[0030] This invention establishes a quantitative mapping relationship between temperature and strength, enabling real-time, non-destructive monitoring of interlayer strength. By conducting independent temperature-strength calibration tests on organic materials before the variable-temperature test and plotting the temperature-strength curve, the corresponding shear strength value can be obtained by mapping the curve after recording the real-time temperature of the weak interlayer during the test. This method eliminates the need for destructive sampling of the interlayer or interruption of the test during the experiment, achieving real-time, continuous, and non-destructive monitoring of the strength of the weak interlayer.

[0031] This invention constructs a multi-dimensional critical condition determination mechanism. By deploying resistance strain gauges at the upper end of the weak interlayer and the slope crest, this invention achieves simultaneous monitoring of local and overall slope displacement. Using a slope crest displacement exceeding 1% of the model height as an objective and quantifiable failure criterion avoids the subjectivity of relying on manual observation to determine the failure moment in traditional methods. Simultaneously, by combining temperature records and temperature-strength curves, the critical temperature and critical strength of the weak interlayer at the time of slope slippage failure can be accurately determined, providing a reliable quantitative basis for slope stability evaluation.

[0032] This invention strictly follows the similarity ratio theory in designing the physical model. The geometric similarity ratio is determined to be 1:300, from which the stress similarity ratio and cohesion similarity ratio are derived to be 1:300, and the internal friction angle similarity ratio to be 1:1. Furthermore, the Froude similarity algorithm is used to calculate the time similarity ratio to be 1:20, ensuring that the geometric, mechanical, and temporal characteristics of the model match the prototype slope height, and that the experimental data have reliable representativeness and extrapolation properties.

[0033] This invention achieves precise shaping and strong interlayer bonding of complex strata in folded development zones. The invention uses a model plate made according to the stratigraphic boundary line to fit the wavy stratigraphic boundary, enabling simultaneous casting and shaping. Simultaneously, by roughening the surface of the cast strata before casting adjacent strata, the bonding force between strata is effectively enhanced, avoiding interference from non-target interlayer slippage on the test results.

[0034] This invention features clear experimental steps and simple operation, demonstrating promising prospects for widespread application. The materials used in this invention, such as EVO organic materials, barite powder, gypsum, and glycerin, are readily available and cost-effective. The operational procedures for model tank preparation, layered casting, and sensor placement are clearly defined and standardized, enabling its widespread application in physical model tests of geotechnical slopes. This provides scientific experimental support for the prevention and control of slope disasters.

[0035] In summary, the method proposed in this invention utilizes the excellent temperature response characteristics of organic materials' mechanical properties. A weak interlayer in a slope is constructed using EVO organic material, and a temperature control device is used to precisely and gradually change the shear strength of the weak interlayer. Simultaneously, a physical model matching the geometry and mechanical properties of the prototype is designed and constructed according to similarity ratio theory. Resistance strain gauges are deployed to monitor the model's displacement and temperature changes, simulating the time-dependent degradation process of the weak interlayer with temperature variations. Ultimately, the critical temperature and strength threshold at which the weak interlayer's strength deteriorates to the point of slope slippage failure are determined. This invention can accurately simulate the time-dependent degradation trend of weak interlayers in slopes, with strong experimental controllability and high data accuracy, providing reliable experimental evidence for slope stability evaluation and disaster prevention in geotechnical engineering. Attached Figure Description

[0036] Figure 1 A schematic diagram of the experimental process for simulating the aging degradation trend of weak interlayers using variable-temperature organic materials, as provided in an embodiment of the present invention.

[0037] Figure 2 This is a schematic diagram of the structure in which the temperature heating wire is spirally laid inside the weak interlayer in an embodiment of the present invention;

[0038] Figure 3 This is a temperature-intensity curve of the organic material (EVO material) in an embodiment of the present invention;

[0039] Figure 4 This is a diagram of the pre-set experimental setup for the model box in an embodiment of the present invention. Detailed Implementation

[0040] The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0041] See Figure 1 This invention provides a method for simulating the aging degradation trend of weak interlayers based on variable-temperature organic materials, including steps such as similarity ratio determination, specimen block calibration, model trench preparation, layered model casting, sensor and temperature control component deployment, model curing, variable-temperature testing, and data monitoring. The method controls the strength of the weak interlayer of organic materials by temperature regulation, and combines this with displacement monitoring to obtain the critical conditions for slope slippage failure. The specific steps are as follows.

[0042] I. Determine the similarity ratio of the physical model

[0043] In this embodiment, the similarity ratio of the physical model is first determined. The prototype slope simulated in this embodiment has a large range, while the actual engineering slope model is approximately 300m in height. The similarity ratio design principle is based on the physical model test of high slopes.

[0044] First, we determine three independent basic similarity ratios for the model (geometric similarity ratio 1:300, density similarity ratio 1:1, and internal friction angle similarity ratio 1:1), and then use these three similarity ratios to derive other similarity ratios.

[0045] Then, under a gravitational field, the self-weight stress at a certain point inside the rock mass is:

[0046]

[0047] in: h

[0048] Substituting the unit weight similarity ratio and geometric similarity ratio into the stress ratios, we obtain a stress similarity ratio of 1:300. Similarly, in rock mechanics, cohesion and stress have the same dimensions. Based on the principle of dimensional consistency, the cohesion similarity ratio is determined to be 1:300. Furthermore, since the friction angle is a dimensionless parameter, dimensionless parameters must be kept consistent in similarity theory; therefore, the internal friction angle similarity ratio is 1:1.

[0049] Finally, the physical model and the prototype must satisfy the similarity of Newton's laws of motion. Based on the similarity ratio determined above, the time similarity ratio is derived. Because...

[0050]

[0051] in:

[0052] Substituting the relevant similarity ratios, the similarity ratio of gravity is 1:300. 3 , and then according to get

[0053]

[0054] in:

[0055]

[0056] The acceleration similarity ratio can be calculated to be 1:1, meaning the model acceleration is consistent with the prototype acceleration. Since the acceleration dimension is LT... −2 ,have to:

[0057]

[0058] in:

[0059] Substituting the acceleration similarity ratio and the geometric similarity ratio, we get a time similarity ratio of approximately 1:20.

[0060] The required similarity ratios for the model experiments are listed in Table 1 below. By setting the similarity ratios as shown in Table 1, the mechanical and temporal similarity of the physical model can be ensured, providing a theoretical basis for the subsequent inversion from model experiment data to the prototype.

[0061] Table 1

[0062] Geometric similarity ratio 1:300 High similarity ratio 1:1 Stress / cohesion similarity ratio 1:300 Similarity ratio of internal friction angle 1:1 Time similarity ratio 1:20

[0063] II. Calibration of Specimen Blocks for Simulated Formation Materials

[0064] In this embodiment, after determining the similarity ratio, the specimen blocks are calibrated. Cylindrical specimen blocks with a radius of 50mm and a height of 100mm are prepared according to a preset ratio of barite powder, gypsum, and glycerin. Three specimens are prepared for each ratio. After curing, uniaxial compression tests are performed to determine the specific gravity, compressive strength, and modulus of elasticity. The simulated strata include limestone, karst breccia, and dolomite; the water content of the materials is a specific proportion of the dry powder, with appropriate amounts of water added to the latter two types of materials based on actual conditions. During the physical model experiment, the bedrock portion (i.e., the lower layer simulating the weak zone) is assumed to remain unchanged and is replaced by a fixed template. The overlying strata are, in order, dolomite, karst breccia, and limestone. The model box structure is as follows: Figure 4 As shown.

[0065] It is worth mentioning that multiple specimen blocks were prepared for each mix ratio (3 blocks per group in this embodiment) to ensure the reliability of the test data and to eliminate random errors by taking the average value. After curing, uniaxial compression tests were conducted to determine the mechanical parameters of each specimen block. Based on the test data, a mix ratio strength curve was plotted. Through repeated comparison and verification using uniaxial compression tests, the mix ratio of the experimental materials was continuously adjusted. While ensuring that the density is close to the actual value, the closer the compressive strength calculated by stress similarity ratio is to the actual value, the more reasonable the material mix ratio is, thus ultimately determining the optimal material mix ratio for each stratum. The role of this mix ratio strength curve is to guide the final selection of the material mix ratio for each stratum in subsequent steps, ensuring that the mechanical parameters of each simulated stratum meet the stress similarity ratio, cohesion similarity ratio, and internal friction angle similarity ratio requirements determined above.

[0066] III. Temperature-strength Pre-calibration of Organic Materials

[0067] Furthermore, before the variable temperature test begins, an independent temperature-strength calibration test must be conducted on the organic materials used in this test. Specifically, standard specimens are prepared using the same EVO organic material mix as that used in the weak interlayer casting, and direct shear tests are performed under different temperature conditions (covering the entire range from 15°C to the estimated failure temperature of 65°C) to determine the shear strength at each temperature point. The test results are plotted as follows: Figure 3 The temperature-strength curve of the organic material is shown. This temperature-strength curve serves as a quantitative basis for inferring the shear strength of the weak interlayer from the real-time temperature in subsequent steps. More specifically, during the variable-temperature test, as long as the temperature of the weak interlayer at the current moment is recorded, the corresponding strength value can be obtained by mapping through this curve.

[0068] In this embodiment, the organic material used is EVO material, scientifically known as ethylene-vinyl alcohol copolymer, which is copolymerized from ethylene and vinyl alcohol structural units. Industrially, it is usually produced by first copolymerizing ethylene and vinyl acetate, followed by a saponification reaction.

[0069] IV. Preparation of the Model Tray

[0070] Continue preparing the model tank. In this embodiment, the model size is 1m×1.6m×0.4m. To ensure the casting operation space and the model forming effect, a model tank with a size of 1.2m×1.7m×0.45m is prepared.

[0071] When preparing the model tank, Vaseline was evenly coated on the glass surface of the side walls to reduce the frictional resistance between the model and the side walls and avoid interference from frictional resistance on the model's displacement and deformation. Grid lines were drawn on the glass side walls to facilitate observation of the overall displacement and deformation of the slope and to provide a reference benchmark for subsequent digital image correlation analysis. A layer of plastic film was laid at the bottom of the model tank to prevent moisture loss from the bottom during the pouring and curing process and to ensure the stability of the model material ratio. At the same time, the layers were marked on the model tank to provide a positioning basis for layered pouring.

[0072] V. Layered casting of the model

[0073] After the model tank is prepared, the model is poured in layers. In this embodiment, based on the final determined material ratios for each layer, combined with the total volume of the model and the density of each material, the required amounts of barite powder, gypsum, glycerin, and water for each layer are precisely calculated. Then, the dry powder materials of each layer are thoroughly mixed according to the calculated ratio, and then the preset amount of glycerin and an appropriate amount of water are added. The mixture is then thoroughly stirred by manual or mechanical stirring to ensure that the materials are mixed evenly.

[0074] It is worth mentioning that, in this embodiment, since the simulated slope strata are in a folded development zone and the strata are wavy, a model plate made according to the strata boundary line is used to fit the strata boundary. Then, the mixed material is poured into the model box for layered pouring. During the pouring process, the model plate is used to compact the strata to ensure that the strata reach the designed thickness, realizing simultaneous pouring and shaping. The model plate has the dual functions of shaping the terrain boundary and compacting the strata.

[0075] It should be noted that the model plate is made of thin iron plate with good plasticity, generally less than 5mm thick, and is manufactured according to the shape of the stratigraphic lines. Specifically, during use, the thin steel plate needs to be bent and shaped accordingly, referring to the stratigraphic line shape drawn on the model box. After pouring one stratigraphic layer, before pouring the next, the surface of the poured layer needs to be roughened to enhance the bonding force between adjacent stratigraphic layers and prevent interlayer slippage. After each stratigraphic layer is poured, the boundary line between that stratigraphic layer and the overlying stratigraphic layer is marked on the side plate of the model tank for easy observation and data verification during the experiment.

[0076] Furthermore, after each layer of soil is poured, a pneumatic device installed in the equipment chamber is used to pre-consolidate the poured soil to achieve the designed density. After pre-consolidation, the pouring of the next layer continues. Once all layers are poured and the weak interlayer is formed, the pneumatic device is activated again to pre-consolidate the entire slope model as a whole, ensuring that the overall mechanical properties of the model meet the test requirements.

[0077] VI. Sensor and Temperature Control Component Layout

[0078] In this embodiment, the sensor and temperature control components need to be deployed simultaneously during the model casting process. Since the monitoring focus of this experiment is on slope displacement and the temperature of the weak interlayer, the strength of the weak interlayer needs to be changed simultaneously through the temperature control components.

[0079] Regarding the placement of the temperature control components, a two-stage pouring method is adopted when casting the EVO organic material weak interlayer: after the first pour of the bottom layer of the weak interlayer is completed, the temperature heating wire is laid flat on top of the bottom layer, and then the top layer of the weak interlayer is poured, thus encasing the temperature heating wire inside the finally formed weak interlayer. (Refer to...) Figure 2 To ensure maximum uniform heating and avoid potential localized overheating or heating blind spots that might occur with straight-line laying, the heating wires are laid in a spiral pattern, with a spacing of 0.1m between the inner and outer layers. The heating wires are connected to an external temperature controller to form a complete temperature control system, enabling precise closed-loop control of the temperature in the weak interlayer. The temperature controller's setting error is ±2℃, and 75℃ is set as a safe temperature to prevent overheating and potential safety hazards during experiments.

[0080] For displacement monitoring, resistance strain gauges were embedded at the upper end of the weak interlayer, and used in conjunction with a data acquisition instrument to monitor local displacement caused by the reduction in the strength of the weak interlayer. Simultaneously, resistance strain gauges were placed at the leading edge, middle, and rear of the weak interlayer to ensure observation of overall displacement field changes. Furthermore, cameras were deployed outside the model box, and digital image correlation technology was used to record the macroscopic situation of slope failure in real time during the experiment, providing visual evidence for subsequent slope failure mode analysis.

[0081] VII. Model Curing

[0082] In this embodiment, after the model is cast, it also needs to be cured. Specifically, after the model is cast, it is placed indoors at a temperature of approximately 25°C and a humidity of approximately 60% for natural curing for one week, until the plaster is completely hydrated and the mechanical properties of the model material reach a stable state. To prevent the simulated rock mass from cracking due to excessive evaporation of moisture during the curing process, plastic wrap can be placed over the model box for moisture retention. After curing, the model can enter the formal variable temperature test stage.

[0083] VIII. Temperature Variable Test and Data Monitoring

[0084] In this embodiment, after the model curing is completed, the temperature control system and displacement monitoring system are activated to debug the test equipment and ensure the accuracy of temperature control and data acquisition. The temperature control system starts from an initial temperature of 15°C and uses a gradient heating method, increasing the temperature by 2°C every 24 hours to ensure that the strength of the weak interlayer deteriorates sufficiently with temperature changes.

[0085] Throughout the temperature control process, slope displacement data collected by each resistance strain gauge was recorded in real time, along with the temperature of the weak interlayer at each time point, establishing a correlation between temperature and displacement over time. The analysis approach of judging slope instability by monitoring abrupt changes in slope displacement, as referenced in the strength reduction method, and considering that the slope crest location is easily determined and its displacement effectively reflects the overall slope stability, was chosen as the key monitoring point in this experiment. To eliminate the influence of model size on the failure displacement, when significant slippage occurred on the slope, i.e., when the displacement at the slope crest increased sharply and its cumulative value exceeded 1% of the total model height, the model was considered to have failed, and the temperature of the weak interlayer at this time was immediately recorded. This was compared with a pre-calibrated temperature-strength correlation for organic materials (e.g., ...). Figure 3 As shown in the figure, the shear strength of the weak interlayer at this temperature is determined, and this strength value is the critical strength of the weak interlayer when the slope undergoes slippage failure.

[0086] This invention is not limited to the above embodiments. The examples and descriptions in the specification are only illustrative of the principles and methods of this invention. Various changes and modifications can be made to this invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of this invention as claimed.

Claims

1. A method for simulating the aging degradation trend of weak interlayers based on variable-temperature organic materials, characterized in that, include: Step 1: Determine the geometric similarity ratio, density similarity ratio, stress similarity ratio, cohesion similarity ratio, internal friction angle similarity ratio, and time similarity ratio of the physical model based on the similarity ratio theory; Step 2: Prepare materials for simulating various lithological strata of the slope, and determine the proportion of materials for each lithological stratum through mechanical tests of specimen blocks; Step 3: Prepare the model trench; pour the lithological strata materials in layers into the model trench, and use organic materials to pour the weak interlayers at the predetermined layers to construct the slope physical model. Step 4: Install heating components inside the weak interlayer and connect the heating components to a temperature controller to form a temperature control system; install resistance strain gauges at the top of the weak interlayer and the slope physical model, respectively. Step 5: Curing the slope physical model; Step 6: Start the temperature control system and raise the temperature of the weak interlayer according to the preset heating rate, while simultaneously recording the displacement data of each resistance strain gauge and the temperature data of the weak interlayer. Step 7: When the slope displacement reaches the preset failure criterion, determine the critical strength of the weak interlayer according to the temperature-strength correspondence of organic materials.

2. The method according to claim 1, characterized in that, The geometric similarity ratio is 1:300; the specific gravity similarity ratio is 1:1; the stress similarity ratio and the cohesion similarity ratio are both 1:300; the internal friction angle similarity ratio is 1:1; and the time similarity ratio is 1:

20. The time similarity ratio is calculated using the Froude similarity algorithm.

3. The method according to claim 1, characterized in that, The mix proportions of materials for each lithological stratum were determined through mechanical tests on specimen blocks. Specifically, cylindrical specimen blocks with a radius of 50 mm and a height of 100 mm were prepared according to a preset mix proportion of barite powder, gypsum, and glycerol. Three specimen blocks were prepared for each mix proportion. After curing, uniaxial compression tests were conducted to determine the specific gravity, compressive strength, and modulus of elasticity. A mix proportion strength curve was plotted to ensure that the specific gravity was close to that of the actual stratum and that the compressive strength, after stress similarity ratio conversion, was close to that of the actual stratum compressive strength. The rock types of the lithological strata materials included limestone, karst breccia, dolomite, soft yellow fill, and weathered soil.

4. The method according to claim 1, characterized in that, The dimensions of the slope physical model are 1m × 1.6m × 0.4m, and the dimensions of the model trench are 1.2m × 1.7m × 0.45m. Preparing the model tank specifically includes: coating the sidewall glass surface of the model tank with Vaseline, drawing grid lines on the sidewall glass, laying a plastic film at the bottom of the model tank, and marking each lithological stratum on the model tank.

5. The method according to claim 1, characterized in that, The process of pouring materials of various lithological strata in layers in the model trench includes: making a model plate according to the stratigraphic boundary line, using the model plate to fit the wavy stratigraphic boundary, pouring and compacting the mixed material in layers; after completing the pouring of one layer of strata, roughening the surface of the poured strata before pouring the next layer; and marking the stratigraphic boundary line on the side plate of the model trench after each layer of strata is poured.

6. The method according to claim 1, characterized in that, The weak interlayer is formed by casting organic materials, specifically including: casting the weak interlayer using a two-stage casting method, the first casting forming the bottom layer of the weak interlayer, the heating component being laid flat on top of the bottom layer, and then the second casting forming the top layer of the weak interlayer, so that the heating component is wrapped inside the weak interlayer.

7. The method according to claim 1, characterized in that, The heating component is a temperature heating wire, which is spirally laid inside the weak interlayer, with a spacing of 0.1m between the inner and outer layers of the spiral laying.

8. The method according to claim 1, characterized in that, Strain gauges are installed at the top of the weak interlayer and the slope physical model, specifically including: installing a strain gauge at the upper end of the weak interlayer, installing one strain gauge at the front edge, middle and rear of the weak interlayer, and installing a strain gauge at the top of the slope.

9. The method according to claim 1, characterized in that, The preset failure criterion is that the displacement at the top of the slope exceeds 1% of the height of the slope physical model.

10. The method according to claim 1, characterized in that, The temperature-strength relationship of the organic material was obtained through a pre-conducted temperature-strength calibration test: standard specimens were made using organic materials with the same proportions as those used in the weak interlayer casting, and direct shear tests were conducted under different temperature conditions to determine the shear strength at each temperature point and plot the temperature-strength curve.

Citation Information

Patent Citations

  • A slope model with weak interlayers and a method for monitoring its deformation during shaping.

    CN113108752B

  • Variable gradient simulation device for slope interface instability caused by soft clamping rock argillization under dry-wet alternation effect

    CN113324988A

  • Ice-rock clastic slope model experiment system under freezing and thawing cycle effect

    CN218956580U